The mapmaker's children : a novel - McCoy, Sarah, 1980- (Crown Publishers, 2015)
"The Mapmaker's Children is the story of Sarah Brown, the vibrant, talented daughter of abolitionist John Brown. Her conventional life trajectory is dynamically changed when she's told the shocking news that she can't bear children and stumbles into her father's work on the Underground Railroad. Realizing that her artistic talents may be able to help save the lives of slaves fleeing north, she becomes one of the movement's leading mapmakers. Since many runaways are unable to read and cannot carry obvious maps demarcating safe houses, Sarah takes her cues from the slave code quilts of her abolitionist colleagues, hiding her maps within her paintings. But joining the mission makes her a target for the same bigotry and hatred that led to the execution of her father and is steering the country toward a bloody civil war. Interwoven with Sarah's adventure is the present-day story of Eden, a modern woman desperate to conceive a child with her husband, who moves to an old house in the suburbs of Washington, D.C. and discovers a porcelain head hidden in the root cellar--the remains of an Underground Railroad doll with an extraordinary past of secret messages, danger and deliverance. Sarah and Eden's connection bridges the past and present, forcing each of them to define courage, family, love and legacy in a new way"--